In situ water column sensor data from NUI dive 046 at the Lucky B hydrothermal field, R/V Polarstern expedition PS137 - Christopher R German (PANGAEA, 2025)
The dataset contains positioning and in situ sensor data collected by the underwater vehicle Nereid Under Ice (NUI) while exploring the hydrothermal plumes of the Lucky B site (81°N, Lena Trough) in June–July 2023 during RV Polarstern expedition PS137. The data span the entire deployment, including an sensing and mapping phases in AUV (Autonomous Underwater Vehicle) mode and a geotransect phase in ROV (Remotely Operated Vehicle) mode. Specifically, the dataset contains temperature, salinity, turbidity, redox-potential, and relative methane concentrations. During NUI extquotesingles water column survey, the primary sensors utilized aboard NUI were the same package routinely used for AUV-based plume surveys (CTD, optical backscatter, and ORP sensors) augmented with a Franatech in situ METS Methane Sensor. The METS sensor was not calibrated, hence providing relative enrichments rather than absolute concentrations of dissolved CH4 in the water column.